Input-output models for sustainable industrial systems : implementation using LINGO /: implementation using LINGO. (2018) - Tan, Raymond R; Aviso, Kathleen B; Promentilla, Michael Angelo B; Yu, Krista Danielle S; Santos, Joost R
No abstract available